2007
DOI: 10.1080/01496390701477063
|View full text |Cite
|
Sign up to set email alerts
|

Removal of API's (Active Pharmaceutical Ingredients) from Organic Solvents by Nanofiltration

Abstract: The removal of 5 specific active pharmaceutical ingredients (API's) with molecular weight of 189, 313, 435, 531, and 721, respectively, from toluene, methylene chloride, and methanol was studied by using solvent resistant nanofiltration. Three membranes of the StarMem series (120, 122, and 228), with cut-off values of 200, 220, and 280 respectively, were used in the experiments. Although the rejections expected from the size difference between solutes and membrane pores are high, the results largely depended o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 19 publications
1
60
0
1
Order By: Relevance
“…A distillation process that recovers 451 tons of methanol annually consumes 162 MWh, which is over 200 times higher than that the energy consumption of the SRNF separation process. 169 A similar conclusion was made by Rundquist et al, 170 which indicated that SRNF showed significant potentials for recovering used solvents in the API crystallization process because of its lower energy consumption compared with that of the conventional distillation. Other reports have focused on pharmaceutical purification processes by combining SRNF with other separation techniques, such as counter-current chromatography.…”
Section: Pharmaceutical Applicationssupporting
confidence: 51%
See 2 more Smart Citations
“…A distillation process that recovers 451 tons of methanol annually consumes 162 MWh, which is over 200 times higher than that the energy consumption of the SRNF separation process. 169 A similar conclusion was made by Rundquist et al, 170 which indicated that SRNF showed significant potentials for recovering used solvents in the API crystallization process because of its lower energy consumption compared with that of the conventional distillation. Other reports have focused on pharmaceutical purification processes by combining SRNF with other separation techniques, such as counter-current chromatography.…”
Section: Pharmaceutical Applicationssupporting
confidence: 51%
“…175 the same authors detailed the design of a two-stage membrane process to completely recover API from methanol. 169 In this system, the actual rejection is 91% with an 80% of recovery rate and 83% observed rejection. The continuous separation process yields only 1.7 ppm of API in the permeate solution.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Separation processes are extremely important in the chemical and pharmaceutical industry since about 50-90% of capital investments in the chemical industry are related to separation processes [1]. In addition, synthesis of active pharmaceutical ingredients (APIs) in the pharmaceutical industry is often carried out in organic solvents and involves the separation of products with high added value from the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…All the advantages of nanofiltration are due to the nanometersized pores and electrical charges on the selective layer. Nanofiltration membranes have wide applications such as water softening, removal of dyes, pesticides and natural organic matter from drinking water, recovery of valuable pharmaceutical products, and removal heavy metal ion from industrial wastewater [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%